2023
DOI: 10.1007/s40948-023-00562-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coal bedding dip angle on hydraulic fracturing crack propagation

Abstract: As a commonly used and effective technology for increasing the permeability of coal–rock reservoirs, hydraulic fracturing has been widely used in engineering sites to realize the efficient exploitation and utilization of gas resources in coal–rock reservoirs. The core of hydraulic fracturing is the initiation, propagation, and path of hydraulic cracks. In this paper, the combination of true triaxial physical test and numerical simulation is used to study the influence of coal bedding characteristics on the cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Shales located deep underground are subjected to high pressure at depth, resulting in a series of reactions and changes. As the depth of burial increases, the pressure on the rock increases, leading to a corresponding increase in its geostress (Aliha et al 2012;Isaza et al 2021;Yang et al 2021). It is found that the complexity of the generated fracture network decreases gradually with the increase of the principal stress difference during the fracturing process.…”
Section: Discussionmentioning
confidence: 99%
“…Shales located deep underground are subjected to high pressure at depth, resulting in a series of reactions and changes. As the depth of burial increases, the pressure on the rock increases, leading to a corresponding increase in its geostress (Aliha et al 2012;Isaza et al 2021;Yang et al 2021). It is found that the complexity of the generated fracture network decreases gradually with the increase of the principal stress difference during the fracturing process.…”
Section: Discussionmentioning
confidence: 99%
“…The contact of hydraulic fracture with the reservoir discontinuities can be reviewed by ABAQUS 131 . Huang et al 132 . used the ABAQUS to study coal reservoir attributes on the hydraulic fracturing propagation characteristics.…”
Section: Types Of Hydraulic Fracturing Numerical Simulationmentioning
confidence: 99%
“…36 Qing et al conducted a theoretical analysis based on the mechanisms and process of hydraulic fracturing to derive pressure parameters applied to high methane low permeability outburst coal seams, and finally came up with a reasonable water injection pressure equation. 37 Huang et al 38 used true triaxial hydraulic fracturing experiments combined with numerical simulation to study the effect of coal seam geological characteristics on hydraulic fracturing crack extension and found that under the same stress conditions, the maximum principal stress has a weaker control on hydraulic fracturing crack extension, while the coal seam inclination angle has a greater control on the crack extension, and moreover, the reasonable layout is more conducive to the development and extension of the cracks. Kang et al 39 used similar materials to simulate coal seams, combined with theoretical analysis and field applications, to study the effect of ground stress on the fracture expansion law of hydraulic fracturing in coal seams (as shown in Figure 5), proposed the optimal arrangement of gas extraction boreholes based on the fracture expansion law under the effect of ground stress, combined hydraulic fracturing and gas extraction according to the characteristics of ground stress and geological structure, and proposed a set of integrated hydraulic fracturing and gas extraction process systems of "selection−judgment− In view of the large uncertainty of the risk of coal and gas outburst, the current outburst risk assessment is still mainly based on gas dynamic accident phenomena or empirical indicators of coal and gas outburst, while the question of whether stress perturbation and structural changes to the coal rock body by pressure during hydraulic fracturing will induce outburst has not been fully confirmed; therefore, further observation and confirmation are needed.…”
Section: Hydraulic Fracturing Technologymentioning
confidence: 99%